Parents' willingness to pay for a COVID-19 vaccine for themselves and their children in the United States - Serkan Catma; Diana Reindl (Taylor & Francis Group, 2021)
Differences in obtaining a vaccine vary based on a multitude of factors including perceptions of vaccine safety, efficacy and willingness to pay (WTP). This study focuses on parent perceptions toward a vaccine for COVID-19 including their WTP decisions for their children and themselves. A mixed methods design using a cross-sectional survey was used to assess the perceptions of US parents, with children under 18, in response to the COVID-19 pandemic. The survey was administered online in November 2020 and 584 final responses were collected. The questionnaire consisted of approximately 37 closed and open-ended questions regarding personal background information; awareness, knowledge, and experience of the virus; perception toward vaccines and COVID-19; and the contingent valuation of a hypothetical COVID-19 vaccine. WTP was found to be higher for children and a direct relationship between the number of children and WTP was observed. Parents were willing to pay US$228-$291 for a vaccine for themselves and US$243-US$321 for their children. A positive impact on WTP was found with self-reported parent health status but not children. The findings of this study have important implications for policy programs which require detailed cost-benefit analyses. WTP for a COVID-19 vaccine is crucial to determine the partial benefits of vaccinating to reduce the risk of repetitive widespread outbreaks.